A Review on Unraveling the Complexity of Autoimmune Skin Disorders: Genetic Influences, Environmental Triggers and Innovative Management Approaches - Nirojini, Palanisamy Sharmila; Vijay, Aishwarya; Raja, Amrutha Bandarapalli; Murugan, Ashwini (Indian Journal of Pharmacy Practice)
An autoimmune condition arises when the immune system erroneously targets and eliminates healthy bodily tissues. This can be preceded by a prolonged asymptomatic phase marked by the presence of auto antibodies. Especially in individuals with a genetic predisposition, these auto antibodies can significantly increase the likelihood, severity, and organ-specific impacts of the disease. There are various autoimmune disorders affecting both mucocutaneous and systemic functions, including conditions like psoriasis, vitiligo, dermatitis herpetiformis, systemic lupus erythematosus, bullous pemphigoid, lichen planus, and alopecia areata. These disorders are characterized by identifiable autoantibodies and susceptibility genes. Identifying individuals at the highest risk and avoiding triggering factors could potentially prevent the development of apparent illnesses. Numerous environmental triggers for autoimmunity have been recognized, including insufficient vitamin D levels, exposure to ultraviolet (UV) radiation, smoking, medications, and others. Treatment for these conditions involves the use of sunscreens, topical or systemic corticosteroids, antimalarials, oral immunosuppressants, and intravenous immunoglobulins.
Keywords: Autoimmune disorders; Psoriasis; Vitiligo; Bullous phemigoid; Systemic Lupus Erythematous; Dermatitis Herpetiformis; Alopecia areata; Immunosuppressant; Corticosteroids